2014
DOI: 10.1128/jvi.00947-14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV-1 Integrase Resistance Mutations When Introduced into SIVmac239 on Susceptibility to Integrase Strand Transfer Inhibitors

Abstract: Studies on the in vitro susceptibility of SIV to integrase strand transfer inhibitors (INSTIs) have been rare. In order to determine the susceptibility of SIVmac239 to INSTIs and characterize the genetic pathways that might lead to drug resistance, we inserted various integrase (IN) mutations that had been selected with HIV under drug pressure with raltegravir (RAL), elvitegravir (EVG), and dolutegravir (DTG) into the IN gene of SIV. We evaluated the effects of these mutations on SIV susceptibility to INSTIs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 70 publications
6
29
0
Order By: Relevance
“…Previous reports by our group and others have shown that INSTIs are capable of inhibiting SIV/simian-tropic HIV (stHIV) replication and infectivity in tissue culture (12)(13)(14). We and others have also shown that INSTIs exhibit potent antiviral activity against SIV in tissue culture studies and in vivo with inhibitory concentrations in the nanomolar range; moreover, SIV that was mutated in IN displayed resistance profiles similar to those of HIV (12)(13)(14).…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Previous reports by our group and others have shown that INSTIs are capable of inhibiting SIV/simian-tropic HIV (stHIV) replication and infectivity in tissue culture (12)(13)(14). We and others have also shown that INSTIs exhibit potent antiviral activity against SIV in tissue culture studies and in vivo with inhibitory concentrations in the nanomolar range; moreover, SIV that was mutated in IN displayed resistance profiles similar to those of HIV (12)(13)(14).…”
mentioning
confidence: 70%
“…The latter substitution has been shown to increase the solubility of recombinant integrase without changing its activity in vitro (18,19). The primer pairs used for site-directed mutagenesis to produce the G118R, G140S, Y143R, Q148R, N155H, and R263K mutations have been described previously (12). The primer pairs for other desired mutations in this study (i.e., E92Q, T97A, and F185H) are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is more difficult to develop resistance to DTG. There is growing evidence that G118R and R263K are two mutations that can engender resistance to DTG (16-19, 37, 41, 46), and both substitutions have also been shown to engender INSTI resistance in simian immunodeficiency virus (47). In this context, minor polymorphisms that vary among subtypes may be able to play a major role in the development of drug resistance.…”
Section: Figmentioning
confidence: 99%